The New Economy: Impact of Financial Digitalization on Ghana’s Public Sector - Adzakor, Wisdom Kofi (Jurnal Perpajakan dan Keuangan Publik, 2024)
This study examines the impact of financial digitalization on Ghana's public sector, highlighting the evolution of digital technologies and their transformative effects on economic operations. Using a qualitative literature review methodology, the study synthesizes existing research to explore the theoretical foundations of digitalization, the implementation of financial digital services in Ghana, and their impact on the public sector. Guided by innovation diffusion theory, the study categorizes the adoption of digital financial solutions into phases: innovators, early adopters, early majority, late majority, and laggards, illustrating the gradual integration of digital innovations within the public sector. Furthermore, it delves into the broader concept of the digital economy, discussing its opportunities and challenges for African nations like Ghana. While digitalization offers significant potential for economic growth and improved public services, addressing challenges such as digital literacy, regulatory frameworks, and job market stability is critical to maximizing its benefits. The study underscores the importance of financial digitalization in driving efficiency and transformation in Ghana's public sector.